Multipath Effects in Building Environment Toward Bandwidth Enhancement for Mobile Communication of 47 GHz Frequency - Andrita Ceriana Eska (JURNAL INFOTEL, 2018)
This paper focused at communication system with multipath effects at building environment. The frequency that used for the communication system was 47 GHz. That frequency possibly used for higher bandwidth at communication system. The condition of communication propagation that used was downlink direction. Mobile station placed at track or street with buildings environment condition. This research analysis was based on transmitter power variation, bandwidth variation, and modulation threshold variation. That analysis produced signal to noise ratio value that was obtained from bandwidth variation and transmitter power variation. The transmitter power variation that used was consists of 0.01 Watt, 0.1 Watt, and 1 Watt. Threshold variations for communication modulation that used was consist of 16 QAM and 64 QAM. As the result such as bandwidth variation showed widened of bandwidth then more decreasing of signal to noise ration value, and more increasing of transmitter power then also more increase of signal to noise ratio value